Genome mining approaches to unveil the full potential of the PGPR isolate Methylobacterium sp. 2A - Grossi, Cecilia Eugenia María (2020)
Genomic analysis has become an established tool in the characterization of plant-beneficialmicrobes since it offers the opportunity to study the full arsenal of a strain. Methylobacteriumsp. 2A is a plant growth-promoting rhizobacteria (PGPR) isolated from roots of potato plantsthat has important biotechnological features such as plant growth promotion and biocontrolactivities. Its genome sequence was previously obtained and, briefly, it has 6.39 Mbcomprising 6,142 coding DNA sequences. A comparative genomic analysis was performedto explore unique features in the 2A genome and its similarity with four related members ofthe genus; a core-genome of 3,650 genes was identified, while 937 genes were exclusive ofthis isolate. In the Methylobacterium sp. 2A assembly, 28 genomic islands were detected(560,218 bp) representing 8.75% of the entire genome. Among the 482 protein-coding geneslocated in the genomic islands, 182 genes encode proteins of unassigned function and 48genes encode transposon-related proteins. Interestingly, the Methylobacterium sp. 2Agenome harbours a horizontally-transferred genomic island that codifies the nodulationprotein nolO which has high similarity to Phaselicystis flava MSr931. We also detectedgenes potentially associated with mercury, arsenic, chromate, and copper/silver resistancethat could be involved in the environmental adaptability of Methylobacterium sp. 2A.Furthermore, we integrated this list with the pan-genome data. The data presented in thiswork provides further valuable information of the Methylobacterium sp. 2A genome to unveilits full potential.